A Method for Improving Joint Strength of Resistance Spot Welds of AA 5182-O Aluminum Alloy. (September 2019) - Wang, Yanjun; Tao, Wu; Yang, Shanglu
Abstract: In this paper, an invented electrode named NewTon Ring (NTR) and the other two Flat Top (FT) electrodes of having 5 mm and 8 mm outer diameter were employed to weld 2 mm AA 5182-O aluminum alloy sheets. The appearance and mechanical performance of the Resistance Spot Welding (RSW) welds obtained using the selected electrodes were investigated. The results showed that the tensile shear and cross-tension strength of the joints obtained by NTR electrode were higher than those obtained by FT electrodes, which have the same outer diameter and contact area compared with NTR respectively. The improvement of the weld strength was attributed to the formation of a bigger weld nugget and spatter-free process achieved by NTR electrode compared to FT electrodes. A new nucleation mechanism was proposed for the weld nugget formation, which was different from the traditional RSW method.